Study and performance analysis of received signal strength indicator (RSSI) in wireless communication systems - F. Mohsin, Hassan; A. Kadhim, Karrar; N. Khudhier, Zaid (International Journal of Engineering and Technology, 2019)
The performance of received signal strength indicator (RSSI), which is an evaluated measure of the received power level in the receiver received by a radio frequency (RF) device from the base station sector, access point, or router, is investigated. Long distance weakens and distorts the signal slows down the wireless data rates, thereby leading to a low throughput data. RF signal is measured by the RSSI, which indicates how well a particular radio device can hear remotely connected client radios and is measured by db. Higher or lower RSSI signal than a specific range is undesirable, and call drop issue or link failure will occur. For example, the maximum RSSI of an indoor multipurpose network range should be âˆ’75 db to âˆ’85 db. This article is organized as follows. The first part presents a brief introduction to the code-division multiple access communication systems. The second part discusses the parameters that affect the quality of RSSI. The third part introduces the practical measurements collected from Iraqcell Telecommunication Company. The fourth part provides the conclusion.Â Â Â